DISTRIBUTION AND MARKETING MARGIN OF MACKEREL SCAD FISH AT TEGALSARI FISHING PORT (CASE STUDY: KM ARJUN PUTRA 02) - Dewi, Priyantini; Gerehem, Billi; Efyjanto, Tonny Kusumo; Mardiah, Ratu Sari; Saputra, Aman; Ridwan (Departemen PSP IPB, 2025)
The marine fisheries sector is a dominant part of the agricultural industry in Tegal City, involving various stakeholders in the production and distribution processes. One of the main challenges in marketing the catch is the price disparity between fishermen and consumers. Therefore, this study aims to identify the distribution patterns of mackerel scad (Decapterus russelli), analyze marketing margins, and evaluate the efficiency of marketing channels at Tegalsari Fishing Port. This research employs a case study method with a descriptive approach to illustrate distribution patterns, as well as calculations of marketing margins and efficiency. The findings reveal the existence of six main marketing channels involving fishermen, collecting traders, wholesalers, retailers, and consumers. The marketing margin ranges from IDR 2,100 to IDR 4,800, with marketing efficiency values between 5% and 11%. Only the first marketing channel is considered efficient, with a value of 5%, while the others have yet to reach optimal efficiency. These results indicate that the marketing efficiency of mackerel scad at Tegalsari Fishing Port still needs improvement to reduce price disparities and enhance the welfare of fishermen and fisheries business actors. Key words: distribution, efficiency, mackerel scad , margin, port